NEGOTIATING EPISTEMIC ASYMMETRY AND POLICY REPAIR: A CONVERSATION ANALYSIS OF THE BILL GATES–MATA NAJWA INTERVIEW ON THE ‘FREE NUTRITIOUS MEAL’ NARRATIVE - Nastainin, Kun; Khoirot Daulay, Irma (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2026)
This study uses Conversation Analysis (CA) to examine the interactional structure of a high-profile media interview between Bill Gates and the Indonesian journalist Najwa Shihab. With a focus on the government’s “Makan bergizi Gratis” (Free Nutritious Meal) programme, the study analyses a seven-minute interaction to understand how epistemic authority is negotiated when political popularity conflicts with scientific efficacy. The findings reveal three distinct interactional patterns. Firstly, the interviewer uses conducive question design, employing prefaced formulations and stance-loaded descriptors (e.g. 'ambitious bet') to project anticipated agreement and solicit validation for domestic policy. Second, the interviewee resists this constraint through 'policy repair'. Gates uses dispreferred turn shapes, such as pauses, meta-pragmatic alerts ('to be frank'), and temporal pivots, to reframe the policy as an early-childhood biological necessity rather than a school-based intervention. Thirdly, epistemic asymmetry is negotiated in public: while the interviewer claims access to political realities, the interviewee asserts epistemic primacy through a 'biological veto', subordinating national framing to evidence-based constraints. This research introduces the concept of